MODEL PERMUKAAN TANAH DIGITAL MULTI DATA UNTUK ANALISIS GENANGAN AIR DI KAMPUS ITB GANESHA - Nur Fauzan, Kamal
Bandung Institute of Technology has a vision as a World Class university. One of the strategy to reach the aforementioned vision is the improvement of international standard education and research infrastructure with the sustainable maintenance. Waterlogging is an infrastructure problem that always happens in ITB Ganesha campus. Digital Terrain Model is used to simulate waterlogging in ITB Ganesha campus. Digital Terrain Model can be created using various methods like LIDAR acquisition, photogrammetry acquisition, and terrestrial acquisition. Integration of all data can be used to improve the accuracy of the DTM. The aim of this research is to make a accurate DTM from the integration of LIDAR, photogrammetry and terrestrial data with Thin Plate Spline transformation method. This study shows that integrated points cloud can be used to make the accurate Digital Terrain Model with 5 cm vertical accuracy around the control point area and 5-20 cm vertical accuracy outside the control point area. The transformation reliability test shows that Thin Plate Spline method has an accuracy of 20 cm. Multi Data Digital Terrain Model is used to make the simulation of flood and waterlogging in certain regions. The simulation fits to the actual condition when the water channel can be modelled by the Digital Terrain Model.